Insect extinctions on a small denuded Bornean island - Sodhi, N.S.; Wilcove, D.S.; Subaraj, R.; Yong, D.L.; Lee, T.M.; Bernard, H.; Lim, S.L.H. (Kluwer (now part of Springer), 2010)
We report odonate and butterfly extinctions on Pulau Mengalum (Sabah) between 1928 and 2007. Pulau Mengalum has lost all of its closed-canopy forest; 55.5% of the odonates and 40% of the butterflies present in 1928 have likely been extirpated. Fourteen and five species of odonates and butterflies found by us were new records for the island, respectively. It is unclear if newly recorded species were missed by previous surveyors in 1928 or if they have colonized the island after that time. While our study indicates that deforestation is a serious threat to tropical insects, it remains unclear if deforested areas provide opportunities for new colonists.